The role of poultry transfers in diet diversity: A cluster randomized intent to treat analysis - Alderman, Harold; Gilligan, Daniel O.; Leight, Jessica; Mulford, M.; Tambet, Heleene (Elsevier, 2022)
Poultry has gained renewed attention as a promising value chain for women because it is an asset that is widely accessible to women, has low start-up costs, and provides a good source of nutritious animal-sourced foods for children in chicken meat and, especially, eggs. The current study presents evidence from an experimental intervention that randomly provided women either a poultry package transfer of vaccinated, improved-breed chickens and related inputs, or a cash grant of equivalent value within a sample of households participating in a social safety net program. These transfers were embedded in a set of intensive livelihood and enhanced nutrition interventions as part of a broader experiment in rural Ethiopia. We assess the impact of the poultry package transfer as well as the enhanced nutrition intervention on the consumption of eggs by both children and adult women. We find that the poultry transfer increased the frequency of egg consumption as well as the sale of eggs, falling between the extreme of an autarkic household and one in which production decisions are fully separable from consumption choices.